Analysis of The Impact of Covid-19 Pandemic on Rupiah Stability and Conposite Stock Price Indeks (IHSG) in Indonesia - Mohammat Saiful Imam; Toha Barizi; Haidar Ali (Enrichment : Journal of Management, 2020)
This study aims to analyze the impact of the Covid-19 pandemic on the stability of the rupiah on the dollar and trading in the Composite Stock Price Index (IHSG). This study uses an SSS analysis tool which is then adjusted to a mathematical equation model. The variables used in this study are macroeconomic variables which include exchange rates, Composite Stock Price Index (IHSG) and Covid-19 which are taken from patient data confirmed positive for Covid-19 every day, with the last 30 days of research. from 30 April 2020 to 29 May 2020. The results of the study concluded that the number of Covid-19 spread had a significant effect on the stability of the Rupiah with a level of influence of 74.5%. And the spread of Covid-19 also has a significant effect on JCI trade with an effect of 68.1%.